Meeting the Technology Challenge: Cost Accounting in a JIT Environment (Book). - Roth, Harold P.; Brief, Richard P. (The Accounting Review, 1989)
Reviews the book "Meeting the Technology Challenge: Cost Accounting in a JIT Environment," by C.J. McNair, William Mosconi and Thomas Norris.